Penampilan Karakter Agronomi Beberapa Genotipe Mutan Padi (Oryza Sativa L.) Baas Selem Generasi Kedua (M2) Hasil Induksi Mutasi - Faihrorrozy; Wayan Sri Suliartini, Ni; Ketut Ngawit, I; Hari Aditia Pratama, Muhammad (Journal of Microbiology, Biotechnology and Conservation, 2025)
This study aims to determine the differences in the appearance of agronomic characters of several genotypes of rice mutants (Oryza Sativa L.) The second generation Baas Selem (M2) is the result of mutation induction. This research was conducted in June 2021 - October 2021 in Nyiur Lembang Village, Narmada District, West Lombok Regency. The methods used were group random design (RAK) and Augmented Design with the treatment used, namely 24 genotypes of second generation Baas Selem rice seeds (M2) with control plants. The control plant repeated 3 times, while the mutant plant was 1 time, in its application using an augmented design. The data obtained were analyzed using ANOVA and BNT at the level of 5%. The results showed that Baas Selem rice mutants differed markedly in all observed agronomic characters, from plant height, flag leaf area, total number of tillers, number of productive tillers, number of grain contained, number of empty grains, weight of grain contained, weight of empty grain, weight of grain 100 seeds, flowering age of harvest age and panicle length.